Dysergonomic risk management model to improve productivity in the liquefied petroleum gas balloon filling process using rula and niosh methodologies - Matamoros Mejia, Claudia Lucero (2024)
The operations in a liquefied petroleum gas plant require risks in the posture of workers during the performance of the operational activities of bottling, which can affect the integrity of the workers, as well as generate excessive operating times and affect productivity. Productivity currently stands at 78%, which is below the company's minimum goal of 85%. Therefore, due to the consequences it generates, it is essential to be a subject of study, so the objective of the research is to improve the productivity of the packaging operation by proposing a dysergonomic risk management model. The evaluation of the criticality of dysergonomic risks by workstation was carried out by means of the Triple Criteria Qualitative Identification and Estimation Matrix in which the activities of injecting liquefied petroleum gas, quality control, sealing and stacking of packaged balloons were defined as those requiring corrective actions due to the adverse effects they cause. The methods for assessing the dysergonomic risks of the activities are carried out by means of the Rapid Upper Limb Assessment (RULA) and the National Institute for Occupational Safety and Health (NIOSH). Finally, there was a 10.4% increase in the productivity of packaged balloons.